2011
DOI: 10.1111/j.1346-8138.2010.01142.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug hypersensitivity: Flare‐up reactions, cross‐reactivity and multiple drug hypersensitivity

Abstract: In drug hypersensitivity, change of drug treatment and continuation with a new drug may result in reappearance of drug hypersensitivity symptoms. This is not uncommon in patients with chronic infections requiring continued and long-lasting antibiotic treatments. For the clinician, the question arises whether these symptoms are due to crossreactivity, are due to a new sensitization or are a reflection of a multiple drug hypersensitivity syndrome. Based on the p-i concept (pharmacological interaction with immune… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
72
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(80 citation statements)
references
References 24 publications
4
72
1
3
Order By: Relevance
“…Coexistence of IgE antibodies in a specific immunological response, for example, in immediate reactions to BLs, has not been proven to date [23], except for anaphylactic reactions to amoxicillin-clavulanic acid, where clinical observations indicate that patients can experience an immediate reaction to both drugs [18]. With respect to T-cell responses to drugs, a number of studies have shown that nonimmediate reactions can occur with chemically unrelated drugs [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Coexistence of IgE antibodies in a specific immunological response, for example, in immediate reactions to BLs, has not been proven to date [23], except for anaphylactic reactions to amoxicillin-clavulanic acid, where clinical observations indicate that patients can experience an immediate reaction to both drugs [18]. With respect to T-cell responses to drugs, a number of studies have shown that nonimmediate reactions can occur with chemically unrelated drugs [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…4 A flare-up reaction, characterized by rapid appearance of symptoms (1-2 days) after treatment with a potential allergic substance in a patient who already shows signs of ongoing drug hypersensitivity is also unlikely, as the patient had an intermittent improvement and as most cases of flare up reactions usually present with an enhancement of the same pre-existing skin lesions (mainly exanthemas). 6 Pustular eruptions or AGEP-like eruptions may appear in relatively few cases of DRESS , but normally at the start and not after remission of DRESS. 7 In severe cases of DRESS and AGEP, large tense bullae and TEN-like lesions can develop which are sometimes very difficult to distinguish among DRESS, AGEP and SJS-TEN.…”
Section: Discussionmentioning
confidence: 99%
“…Flare up reactions are defined as the exacerbation of an existing drug hypersensitivity by introduction of an unrelated drug. [2] This has been reported in Severe Cutaneous Adverse Reactions (SCAR), especially Drug Reaction with Eosinophilia and Systemic Symptoms (DRESS) and is attributed to the immune activation induced by a severe drug reaction, which predisposes the patient to manifest hypersensitivity to otherwise well tolerated drugs.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Cross reactivity arises from structural similarities, common metabolic pathways or pharmacologic mechanisms shared by different drugs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation